The maritime shipment of LNG to Europe: dynamics in markets, ships and terminal projects. (1st January 2012) - Wang, Siyuan; Notteboom, Theo
The aim of this paper is to explore how the maritime shipment of liquefied natural gas (LNG) to Europe has developed over the last decade, given the growing usage of natural gas and increasing seaborne trade volume of LNG over the world. This paper presents the current situation of the LNG trade flows in Europe and also investigates the dynamics of the LNG shipping market, fleet development and import terminal projects in Europe, which are all indispensable to transport LNG to the European market. It is found that Europe increases LNG imports largely in recent years in order to secure its gas supply for seasonal fluctuations. Responding to such rising import volume, many new facilities are being built and planned in the region, including the ordering of new ships and the construction of new regasification terminals.